Voices from the virtual classroom: students' views toward ethical challenges in the context of online formative assessment - Alireza Maleki (Discover Education)
Abstract The global impact of the COVID-19 pandemic has prompted a significant shift toward online Education. However, this transition has raised concerns about assessment, distance learning effectiveness, and student workload. These pandemic-induced conditions may also lead to ethical challenges in education. Despite existing research on ethical issues in online education, the focus on ethical challenges related to online formative assessment, especially in English as a Foreign Language (EFL) contexts, is still limited. Therefore, this study aims to explore students' perspectives on ethical challenges related to online formative assessment. To achieve this objective, a mixed-methods approach was employed. Initially, a qualitative phase involving online focus group discussions was conducted with three distinct groups of eight Iranian EFL learners. These groups encompassed EFL learners from universities, institutes, and schools. Each group participated in a 70-min online discussion to examine the ethical challenges they encountered in online formative assessment following the onset of the COVID-19 pandemic. Thematic analysis of the data revealed that ethical challenges could be categorized into three main areas: group work, feedback, and cheating. Subsequently, a ranking scale was employed to determine the primary category that presented the most significant ethical challenge based on students' viewpoints. The findings indicated that feedback was perceived as the most pressing ethical challenge, followed by issues with cheating and group work categories. Finally, the gathered information was categorized based on the specific learning contexts of the participants. This research provides valuable insights for EFL teachers, policymakers, and educational assessment systems. Based on these findings, it is recommended that EFL teachers and policymakers implement targeted professional development programs, foster a culture of academic integrity, and adopt clear guidelines to address these ethical challenges.